Mesenchymal stem cells protect the integrity of the alveolar epithelial barrier through extracellular vesicles by inhibiting MAPK-mediated necroptosis - Tao Ruan; Jiaming Han; Chengxu Xue; Fengyuan Wang; Juntang Lin (Stem Cell Research & Therapy)
Abstract Background Alveolar‒capillary barrier disruption is a hallmark of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). The contribution of necroptosis to the compromised alveolar-barrier in ALI remains unclear. Mesenchymal stem cells (MSCs) may contribute to tissue repair in ALI and ARDS. Here we evaluated the efficacy and explored the molecular mechanisms of menstrual blood-derived endometrial stem cells (MenSCs) and MenSC-derived extracellular vesicles (MenSC-EVs) in ALI-induced alveolar epithelial barrier dysfunction. Methods Human lung epithelial cells were stimulated with endotoxin and treated with MenSCs or MenSC-EVs, and their barrier properties were evaluated. Lipopolysaccharide (LPS)-injured mice were treated with MenSCs or MSC-EVs, and the degree of lung injury and the alveolar epithelial barrier of the lung tissue were assessed. Results We found that MenSCs reduced lung injury and restored alveolar-barrier integrity in lung tissue. In vitro, MenSCs reduced paracellular permeability and restored barrier integrity in human lung epithelial cells. MenSC-EVs replicated all these MenSC-mediated changes. Mechanistic research revealed that MenSCs inhibited MAPK signaling and necroptosis. JNK inhibition SP600125, and ERK inhibition U0126 or inhibition of necroptosis with Nec-1 or GSK872 diminished the beneficial anti-epithelial barrier dysfunction effects of MenSCs or MenSC-EVs. Conclusions Our results suggest that human menstrual blood-derived endometrial stem cells mitigate lung injury and improve alveolar barrier properties by inhibiting MAPK-mediated necroptosis through extracellular vesicles, supporting the application of MenSCs or MenSC-derived extracellular vesicles to treat ALI or ARDS.